(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article examines aspects of the reliability and environmental safety of gas station equipment. The relevance of the topic is due to the growing requirements to reduce the negative impact on the environment, as well as the need to ensure trouble-free and safe operation of process equipment. The main types of gas station equipment, typical risks associated with its use, and possible ways to minimize emergency situations are considered. The influence of operational factors on the durability and environmental friendliness of equipment is analyzed. Recommendations are offered for modernizing control systems, using innovative technologies and introducing environmentally friendly solutions at gas stations.